(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the types of risks and methods for assessing them based on international experiences. Specifically, it examines the assessment methods corresponding to each type of risk, as well as their advantages, disadvantages, and benefits. The main findings presented in the article have theoretical significance and can be widely applied in financial mathematics. Additionally, the types of financial risks and methods for assessing them based on international experiences can be useful for students in higher education, particularly those studying economics, for calculating specific financial operations.